Artificial Intelligence and its influence on Auditing Processes in large auditing companies in Lima 2023 - Seminario Sotomayor, Abigail (2024)
The objective of this research article is to determine the impact of Artificial Intelligence (AI) on auditing processes in large audit firms in Lima 2023. As is well known, companies are exposed to various administrative and financial problems, with fraud being the most recurrent problem. Therefore, technological advances can detect irregularities and provide companies and auditors with a greater ability to proactively prevent and address fraud. By implementing Artificial Intelligence in auditing processes, auditing companies in Lima will be able to optimize time, detect accounting fraud, provide reliable data, and reduce human errors, without replacing them, since the intervention of an auditor is essential to verify that everything is done in a transparent manner, and then make the best decisions with minimal risks. This is also an advantage for companies in the long term to reduce their costs and increase their productivity. It is worth noting that, currently, the four largest audit firms in Lima are already using AI; however, we will focus on analyzing how the use of this tool impacts the companies. It is important to point out that this sector was chosen due to the magnitude of data they handle, the complexity of the processes and the high competitiveness in the market. The methodology used was qualitative, with a non-experimental design, and interviews were conducted with the collaborators of the most renowned auditing companies in Lima. As for the results, they showed that Artificial Intelligence has become a useful tool for auditors, because thanks to its use, the workload has been reduced and frauds have been detected in advance, making them more productive for the companies. However, this tool does not replace the auditor, since, being a software, it does not have the ability to judge or verbally communicate the results. Finally, it was concluded that AI is a tool that has made it possible to enhance the work of auditing companies and improve their efficiency.